Pulses Model of Electrical Discharge Machining (EDM) - Ade Erawan Minhat; Nor Hisham Hj Khamis; Azli Yahya; Trias Andromeda; Kartiko Nugroho (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This article presents a model of pulses inElectrical Discharge Machining (EDM) system. There areseveral mathematical models have been successfully developedbased on the initial, ignition and discharge phase of currentand voltage gap. According to these models, the circuitschematic of transistor pulse power generator has beendesigned using electrical model in Matlab Simulink software toidentify the profile of voltage and current during machiningprocess. Then, the simulation results are compared withexperimental results.